1987
DOI: 10.1152/ajpregu.1987.253.2.r344
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and body temperature during free diving of Weddell seals

Abstract: We have developed and successfully used the first microprocessor-controlled monitors for collection of data on depth, heart rate, and body temperature of one fetal and five adult male freely swimming Weddell seals. Adult seals almost invariably experienced a prompt bradycardia at the start of each dive, and the mean heart rate during diving was significantly lower for dives greater than 20 min (P greater than 0.999). The heart rate was also significantly greater during the ascent portion of dives when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 0 publications
11
93
1
Order By: Relevance
“…In dives greater than 6 min in duration, minimum ƒ H was usually less than 10 beats min −1 and sometimes as low as 6 beats mins −1 (Fig. 5B), which is similar to extreme divers such as emperor penguins (3 beats min −1 ), elephant seals (3 beats min −1 ), grey seals (2 beats min ), and even as low as what was observed in forced submersion studies (Scholander, 1940;Hill et al, 1987;Thompson and Fedak, 1993;Andrews et al, 1997;Meir et al, 2008). Thus, similar to phocids, the extreme bradycardia exhibited during forced submersions is also a routine component of the sea lion's physiological repertoire, allowing them to perform long-duration dives.…”
Section: Research Articlesupporting
confidence: 67%
See 2 more Smart Citations
“…In dives greater than 6 min in duration, minimum ƒ H was usually less than 10 beats min −1 and sometimes as low as 6 beats mins −1 (Fig. 5B), which is similar to extreme divers such as emperor penguins (3 beats min −1 ), elephant seals (3 beats min −1 ), grey seals (2 beats min ), and even as low as what was observed in forced submersion studies (Scholander, 1940;Hill et al, 1987;Thompson and Fedak, 1993;Andrews et al, 1997;Meir et al, 2008). Thus, similar to phocids, the extreme bradycardia exhibited during forced submersions is also a routine component of the sea lion's physiological repertoire, allowing them to perform long-duration dives.…”
Section: Research Articlesupporting
confidence: 67%
“…As in other freely diving mammals and penguins studied (Millard et al, 1973;Hill et al, 1987;Thompson and Fedak, 1993;Andrews et al, 1997;Boyd et al, 1999;Williams et al, 1999;Green et al, 2003;Froget et al, 2004;Meir et al, 2008), California sea lions also exhibited a gradual tachycardia as they began ascent, with the rate of increase escalating during the last 15-30 s of the dive. It has been proposed that the ascent tachycardia may increase blood flow and O 2 delivery to O 2 -depleted tissues, thus lowering the P O2 in the blood and increasing the blood/lung O 2 gradient, resulting in shorter surface intervals by maximisation of O 2 uptake at the surface (Thompson and Fedak, 1993).…”
Section: Research Articlementioning
confidence: 71%
See 1 more Smart Citation
“…Regardless of such shortcomings, thermometry remains an inexpensive, fast, and attractive method for body temperature recording, especially when cross-sectional data are desirable and subjects can be caught and measured with relative ease. With larger animals, measurements of blood and muscle temperature may be made by percutaneous insertion of a thermistor via a catheter and temperature logged with a surface-mounted recorder [33][34][35]. This allows for continuous monitoring of body temperature while animals are exhibiting natural behaviours but requires recapture of the animal for removal of instrument.…”
Section: Thermometrymentioning
confidence: 99%
“…Combined with the relatively mild bradycardias of free-diving Weddell seals (Hill et al, 1987), this finding suggested that muscle blood flow persisted to some degree during free dives and that the blood O 2 store was not isolated from muscle. This contrasted with the severe bradycardia and peripheral vasoconstriction during forced submersions.…”
Section: Free Dives -Sealsmentioning
confidence: 98%